-4x-49=(x-4)

Simple and best practice solution for -4x-49=(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-49=(x-4) equation:



-4x-49=(x-4)
We move all terms to the left:
-4x-49-((x-4))=0
We calculate terms in parentheses: -((x-4)), so:
(x-4)
We get rid of parentheses
x-4
Back to the equation:
-(x-4)
We get rid of parentheses
-4x-x+4-49=0
We add all the numbers together, and all the variables
-5x-45=0
We move all terms containing x to the left, all other terms to the right
-5x=45
x=45/-5
x=-9

See similar equations:

| 7b=1 | | 5(-5x-9)=255 | | 7-10x=2+6x | | 4m+3.4=2m-11 | | -5-8x=-21 | | 10x+45=-21+26 | | 15-6m=10m+7 | | 2x-9+7=8+x | | 50-3n=7n+18 | | 200=30*4+.10x | | 2=h4− 1 | | –m=4−m | | 16y-5=137 | | -2x-4(3x-1)=-15x+7+x | | 31-4x=71 | | 200=30*4+10x | | x-36=144 | | 5(5x-15=50 | | 10x+45=47 | | x-26=144 | | 3x+34=16 | | -3(5n-4)=-33 | | 2(3-r)=8-6-2r=8-2r=14 | | -9+3x=39 | | -4x-0=17 | | –6g=–7g+g | | x5+5=10 | | t/8+4=2 | | 3/4x+2=5/4x-24 | | 2z+2=6z-30 | | 2(2-5g)=13 | | 7x-4+1x=-1+13x+7 |

Equations solver categories